Conversion of Waste Plastic to Oils for Tribological Applications - Soumya Sikdar; Arpith Siddaiah; Pradeep L. Menezes (Lubricants, 2020)
Plastics are widely used owing to their light weight, easy production, and low cost. Even though plastics find application in different fields of industries and households, they do not degrade easily. If plastics are not disposed of appropriately, it has been shown that they cause widespread environmental pollution, which poses risks to human health. Recycling waste plastics has been an alternative to mitigating plastic pollution, which usually requires high labour costs and produces contaminated water during processing. If plastic recycling will contribute to the development of tribological products like lubricating oils, it is a safer alternative to disposing of plastics in the environment. In order to understand the tribological use of plastics by recycling, the present study reviews different techniques that can be employed to transform waste plastics into petroleum-based oils. The viscosity, density, and friction of pyrolyzed waste plastic oils are investigated and compared with commercial lubricants to assess their potential lubrication applications. The segregation processes, catalytic isomerization dewaxing, and Fischer–Tropsch method to recycle waste plastics are also reviewed to provide an insight into the methods to transform pyrolyzed waste plastic into lubricants.